Energy–water nexus analysis in the Beijing–Tianjin–Hebei region: Case of electricity sector. (October 2018) - Sun, Li; Pan, Bolin; Gu, Alun; Lu, Hui; Wang, Wei
Abstract: Water shortage can constrain energy development and use, and climate change partially caused by energy consumption can profoundly affect the quantity and distribution of water resources worldwide. The chronic water shortage in the Beijing–Tianjin–Hebei region of China is likely to worsen under the impact of global climate change. The coal-dominated electricity sector will continuously have a high water demand. This reality will intensify the dilemma between water supply and power generation. This paper presents an adaptability analysis of the Beijing–Tianjin–Hebei region in 2013–2030 based on the current situation. Water evaluation and planning and long-range energy alternative planning systems are used to simulate changes in water and energy systems, respectively, and the impacts on the electricity sector under two climate scenarios and three development scenarios. On this basis, this study explores the potential of power structure adjustment and technological advancement in easing baseline water stress and promoting sustainable development in the region. Findings show that the Beijing–Tianjin–Hebei region is under high water stress, which will be aggravated under global climate change. In representative concentration pathway (RCP) 4.5 and RCP 8.5 scenarios, the baseline water stress of the region in 2017–2030 averages 259% and 494%, and the annual unmet water demand reaches 15.3 and 21.1 billion m 3, respectively. In the renewable energy and advanced technology scenarios, the regional water savings are expected to reach 200–250 million m 3 by 2030. The unmet water demand of power generation can be alleviated to some extent, but the water shortage trend cannot be reversed. Therefore, the Beijing–Tianjin–Hebei region should develop an overall plan and layout of energy and water resources and adopt a combination of policy instruments to support the expansion of renewable energy or promote advanced power generation technologies. Highlights: Estimate the high water stress in Beijing–Tianjin–Hebei region. Explore Energy–water nexus Analysis of Electricity Sector in the Beijing–Tianjin–Hebei Region. Analysis the potential of power structure adjustment and technological advancement in easing water stress. Beijing–Tianjin–Hebei region should develop an overall plan and layout of energy and water resources.